Belajar Melestarikan Tarian Daerah Pada Usia Dini Di PAUD Ar-Rohmah Kampung Dabatan, Misool Selatan - Nur, Galuh Fitriani; Silviyani; Syalviana, Evie (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2023)
Students have a strategic role as part of agents of change. The Field Experience Program (PPL) is a program that is a training venue for applying various knowledge, attitudes and skills in the context of forming professional students. Therefore, students gain generative abilities in the form of life skills. Observations were carried out by means of discussions and direct involvement in the community. Based on the results of observations, it has been determined that the implementation of PPL includes physical and non-physical programs. One of the work programs that has been implemented is preserving regional dances in Dabatan Village, South Misool in 2023. The research method used in this research is descriptive research method. This descriptive research method is aimed at obtaining answers related to the analysis of the implementation of regional dance preservation in 2023 so that the discussion uses descriptive words. Through descriptive research, this research tries to find an appropriate and sufficient description of the implementation. Judging from the implementation of this program, students act as facilitators, dynamists and motivators. This work program was held for one day, starting from November 9 2023, running relatively smoothly. Thus, after the implementation ends, it is hoped that they can foster a sense of love for their respective regional dances, so that negative behavior towards children and teenagers in South Misool can be overcome.